The administration of long-term high-fat diet in ovariectomized wistar rat (Study on Daily Food Intake, Lee Index, Abdominal Fat Mass and Leptin Serum Levels) - Dita Fitriani; Andreanyta Meliala; Denny Agustiningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACT Leptin and estrogen have an important role in energy homeostasis through anorexic effects on the central nervous system. These hormones can decrease food intake, increases energy expenditure and thermogenesis. Long-term high-fat diet can lead to impaired leptin function. Moreover, estrogen, deficiency is a risk factor of obesity in menopause. The aim of this study is to investigate the effect of long-term high-fat diet on leptin serum levels in ovariectomized rats. Twenty-eight female Wistar rats (Rattus norvegicus) aged 6-8 weeks with body weight 120-150 g were used in this study. Rats were divided into 4 groups i.e. OVXSC groups: rat were ovariectomized and given a standard diet; OVXH groups: rat were ovariectomized and given a high-fat diet; SHAMSC groups: rat were not ovariectomized and given a standard diet; SHAMHF groups : rat were not ovariectomized and given a high-fat diet. Pre-post test with control group design for measurement of serum leptin levels, food intake, and Lee index. While post-test only control group design for measurement of abdominal fat mass. Pearson test was used to analyze the correlation between leptin serum levels, food intake, Lee index and abdominal fat mass. Paired t-test was used to analyze the differences between values before and after being treated. The daily food intake dropped in rat fed a high-fat diet although it was not statistically significant (p>0.05). Ovariectomy significantly increase Lee index (p<0.05). Obesity occurs in ovariectomized group, both of high-fat diet and standard diet. Abdominal fat mass was significantly higher in high-fat compared to standard diet group (p<0.05). Increase in levels of serum leptin highest in OVX-HF group (16.45 ± 8.75 ng/mL), and the lowest in the SHAM-SC (2.98 ± 1.61 ng/mL). In conclusion, serum leptin levels positively correlated with Lee index and abdominal fat mass, but negatively correlated with daily food intake.